Effect of Release Timing of App Innovations based on Mobile Platform Innovations. Issue 4 (1st October 2020) - Soh, Franck; Grover, Varun
ABSTRACT: This study focuses on app innovations based on mobile platform innovations (MPIs), examining how app developers can time the app innovations release to best leverage MPIs and increase app financial performance. We suggest that the performance is contingent on the adoption curve of mobile platform generations and the level of backward compatibility of the MPIs. We find support for our hypotheses after analyzing 1, 213 MPI-based app innovations on the iOS mobile platform ecosystem. The main theoretical contribution of this study, supported empirically, is to better understand the role of the platform generation adoption curve and MPIs' level of backward compatibility in the assessment of the effect of MPI-based app innovation release timing on complementor's performance. We encourage third-party developers to create MPI-based app innovations more prominently and release them early during the growth stage of the adoption curve while prioritizing MPIs with no backward compatibility.